Maintaining the value of influenza vaccination – the shift from quadrivalent to trivalent vaccines: an expert review - David Fisman; Alberto Pérez-Rubio; Maarten Postma; Darvin S. Smith; Joaquin Mould-Quevedo (Expert Review of Vaccines)
Introduction This review provides an expert perspective on the sustained value of seasonal influenza vaccines as they transition from quadrivalent to trivalent formulations, based on apparent elimination of the B/Yamagata strain from circulation and subsequent advice from the World Health Organization (WHO) to remove the B/Yamagata antigen from influenza vaccines. Influenza has a high clinical and economic burden globally. However, coronavirus disease 2019 has created new challenges for managing seasonal influenza by amplifying vaccine hesitancy. Understanding why influenza virus circulation is monitored and vaccines subsequently updated is important for all relevant stakeholders to maintain confidence in the value of seasonal influenza vaccination.Areas covered Discussion is provided on the dynamic nature of communicable diseases, influenza virus monitoring and WHO vaccine composition guidance, and maintaining the value of influenza vaccination to individuals, society, and healthcare systems.Expert opinion The move from quadrivalent to trivalent influenza vaccines is a result of findings from strain surveillance. Continued surveillance and targeting of vaccines against strains most commonly in circulation to keep effectiveness high, and ensure the highest value of vaccination is vital to prevent influenza infection and severe illness, thus reducing pressure on healthcare systems and reducing the economic impact of influenza outbreaks.